2022
DOI: 10.1002/jhet.4543
|View full text |Cite
|
Sign up to set email alerts
|

A green approach for the catalyst‐free synthesis of imidazole‐bearing pyrazole moiety using PEG‐400 as an efficient recyclable medium as potential anti‐tubercular and anti‐microbial agents

Abstract: Polyethylene glycol-400 (PEG-400) is a recyclable and rapid reaction medium for synthesizing a new series of 4-(3-[substitutedphenyl]-4,5-dihydro-1-phenyl-1H-pyrazol-5-yl)-1H-imidazoles in two-step procedures by condensation of 1H-imidazole-4-carbaldehyde and various acetophenones to form chalcones followed by base-catalyzed cyclization employing phenyl hydrazine in a catalyst-free approach. The way of projected approach provides easy work-up, less reaction time, avoids metal-based and toxic catalysts, high yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The synthesized pyrazole derivatives were screened for their anti-tubercular activity and it was shown that the compound 501a was most active with inhibition of 98.17 and 94.37 % at the concentration of 12.5 μg/mL in dormant and active stages respectively. (Scheme 96) [111] Malhi et al noted the synthesis of different selenosemicarbazones which were produced by the combination of cylcohexanoneselenosemicarbazone with aldehydes and ketones. Furthermore, the developed selenosemicarbazones were examined for their potential anti-tubercular activity and the result pointed out that many of the synthesized products showed excellent activity with MIC value of 1.6 μg/mL.…”
Section: Ms Komal Saini Has Been Working As Anmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesized pyrazole derivatives were screened for their anti-tubercular activity and it was shown that the compound 501a was most active with inhibition of 98.17 and 94.37 % at the concentration of 12.5 μg/mL in dormant and active stages respectively. (Scheme 96) [111] Malhi et al noted the synthesis of different selenosemicarbazones which were produced by the combination of cylcohexanoneselenosemicarbazone with aldehydes and ketones. Furthermore, the developed selenosemicarbazones were examined for their potential anti-tubercular activity and the result pointed out that many of the synthesized products showed excellent activity with MIC value of 1.6 μg/mL.…”
Section: Ms Komal Saini Has Been Working As Anmentioning
confidence: 99%
“…The synthesized pyrazole derivatives were screened for their anti‐tubercular activity and it was shown that the compound 501a was most active with inhibition of 98.17 and 94.37 % at the concentration of 12.5 μg/mL in dormant and active stages respectively. (Scheme 96) [111] …”
Section: Chemistry Of Different Heterocycle Scaffolds As Antitubercul...mentioning
confidence: 99%
“…The synthesized crude 4 a-4 j were tested for their activity against various Gram-positive bacteria like Bacillus subtilis MTCC121, Staphylococcus aureus MTCC 96, staphylococcus MLS-16 MTCC2940, Micrococcus luteus MTCC2470 and Gram-negative bacteria like Escherichia coli MTCC739, Pseudomonas aeruginosa MTCC2453, Klebsiella planticola MTCC530 taking chloramphenicol as a positive control, and Candida albicans MTCC3017 strain used for anti-fungal strain using nystatin as the positive control (Table 3 and Figure 2). [27][28][29] Scheme 2. Plausible mechanism for the A 3 coupling reaction by Gold catalyst.…”
Section: In Vitro Study For Antimicrobial Activitymentioning
confidence: 99%
“…Our group is continuously working to generate a new scaffold based on nitrogen-rich heterocycles and to identify lead in the thrust area of medicinal chemistry in which a real "Hitmen" like molecules are synthesized by applying hybridization of two or more active heterocycles concept [20][21][22][23][24]. Herein, we report the four-step synthetic strategy starting from easily accessible substrate, that is, methyl 3,4-diaminobenzoate to afford the high yielded regioselective adducts, 5-(5-amino-1H-pyrazol-3-yl)-1,-3-dimethyl-1,3-dihydro-2H-benzo[d]imidazol-2-one derivatives (5a-l).…”
Section: Introductionmentioning
confidence: 99%